Determination of Heavy Metals through Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) in Iranian Cheese and Their Potential Health Risks to the Adult Consumers - Elham Baseri; Mahmood Alimohammadi; Ramin Nabizadeh Nodehi; Shahrokh Nazmara; Gholamreza Jahed khaniki; Mohamad Es'haghi Gorji (Iranian Journal of Health, Safety and Environment, 2017)
In Iran, cheese is one of the dairy products that widely consumed as a main diet for breakfast. Moreover, trace metals in dairy products have recently gained considerable attention. Iranian cheese samples were collected from Tehran, Iran (February to May 2013). Trace metals including Pb, Cd, Ni, Fe, Sn, Zn, Cr, and Cu were analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES) after dry ashing. All the tested metals were detected in the cheese samples. The mean concentration of metals in cheese showed the following decreasing order Zn > Fe > Cu > Ni > Sn > Cr > Pb > Cd, with values of 12.98, 7.95, 1.96, 0.83, 0.46, 0.37, 0.34, and 0.01 mg/kg, respectively. There were no significant differences between types of cheese samples in terms of content of trace metals (p>0.05). All the samples had Pb contents of greater than Codex limit (0.02 mg/kg). According to the measured values of the metals in this study, the intake of all the studied elements through the common consumption of cheese in Iran was below the dangerous level according to permissible intake value for each metal. Also, levels of correlations between the element pairs were analyzed.